Conceptual Design of a Novel Biomimetic Underwater Robot - Volanis, Georgios; Stavroulakis, Georgios E.; Oungrinis, Konstantinos-Alketas (Applications of Modelling and Simulation, 2020)
By defining the limits and the design specification, that an underwater robotic vehicle should fulfill in order to be characterized as biomimetic, a shell structure with a modular locomotion mechanism is proposed, using THUNDER piezoelectric, for a novel biomimetic underwater robot. Smart materials and especially piezoelectric actuators are an excellent alternative as a propulsion mechanism for our underwater swimming fish-like robot (SRFL swimming robot with fish-like locomotion), due to their unique characteristics. This paper presents the design characteristics, the restrictions in dimensions and weight of the underwater robot and the ability of it, for maneuverability. Furthermore, the articulated locomotion mechanism of the caudal fin is designed and analyzed, while the distribution of the pressure forces on the shell, as well as in the articulated mechanism of the tail fin is also determined. Finally, the articulated mechanism is represented in MATLAB/SIMSCAPE in order to simulate the locomotion of the tail fin, giving us the average speed and acceleration.